2017
DOI: 10.1038/bjc.2017.26
|View full text |Cite
|
Sign up to set email alerts
|

PET/MR in invasive ductal breast cancer: correlation between imaging markers and histological phenotype

Abstract: Background:Differences in genetics and receptor expression (phenotypes) of invasive ductal breast cancer (IDC) impact on prognosis and treatment response. Immunohistochemistry (IHC), the most used technique for IDC phenotyping, has some limitations including its invasiveness. We explored the possibility of contrast-enhanced positron emission tomography magnetic resonance (CE-FDG PET/MR) to discriminate IDC phenotypes.Methods:21 IDC patients with IHC assessment of oestrogen receptor (ER), progesterone receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 43 publications
4
33
0
Order By: Relevance
“…The authors found that estrogen receptor (ER) and progesterone receptor (PR)‐negative tumors had higher SUV max and K ep than ER or PR‐positive tumors; that HER2‐negative tumors had higher apparent diffusion coefficient (ADC) mean , K ep , and SUV max values; and that tumors with lower levels of Ki67 showed lower ADC mean , but not greater K trans , as seen in the Margolis et al study . PET/MR markers correlated with immunohistochemical (IHC) phenotype in 62%, a promising beginning …”
Section: Index Lesion Evaluationmentioning
confidence: 80%
See 1 more Smart Citation
“…The authors found that estrogen receptor (ER) and progesterone receptor (PR)‐negative tumors had higher SUV max and K ep than ER or PR‐positive tumors; that HER2‐negative tumors had higher apparent diffusion coefficient (ADC) mean , K ep , and SUV max values; and that tumors with lower levels of Ki67 showed lower ADC mean , but not greater K trans , as seen in the Margolis et al study . PET/MR markers correlated with immunohistochemical (IHC) phenotype in 62%, a promising beginning …”
Section: Index Lesion Evaluationmentioning
confidence: 80%
“…Catalano et al investigated whether 18 F‐FDG PET/MR could differentiate between histological phenotypes of breast cancer in 21 patients with invasive ductal carcinoma (IDC) . The authors found that estrogen receptor (ER) and progesterone receptor (PR)‐negative tumors had higher SUV max and K ep than ER or PR‐positive tumors; that HER2‐negative tumors had higher apparent diffusion coefficient (ADC) mean , K ep , and SUV max values; and that tumors with lower levels of Ki67 showed lower ADC mean , but not greater K trans , as seen in the Margolis et al study .…”
Section: Index Lesion Evaluationmentioning
confidence: 99%
“…From this, the areas where evidence exists that PET/MRI has been demonstrated to provide better information and characterisation of disease are in prostate cancer [ 23 ] and, as suggested previously at these workshops, in paediatric oncology [ 42 ]. Areas where new evidence is emerging include gastrointestinal cancers [ 43 , 44 ], breast cancer [ 40 , 41 ], gynaecological malignancies [ 37 ] and hepato-pancreatobiliary cancers [ 45 ]. The value of PET/MRI in these applications was seen again to be in a comprehensive regional evaluation and not in “whole-body” applications; as stated by one of the panellists: “The added value of PET/MRI starts locally”.…”
Section: Dialogue Boardsmentioning
confidence: 99%
“…The pharmacokinetic DCE-MRI parameters can be further correlated with metastatic status, Ki67 expression ( 38 ), and prognosis ( 39 , 40 ). Catalano et al demonstrated that 18 F-FDG PET/MRI could distinguish between molecular subtypes in 13/21 breast cancer patients ( 41 ).…”
Section: Pet-based Imaging Techniquesmentioning
confidence: 99%